2016
DOI: 10.1007/s10578-016-0675-y
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Cognitive Behavior Therapy for School Refusal with Fluoxetine: A Randomized Controlled Trial

Abstract: This study investigates whether the augmentation of cognitive behavior therapy (CBT) with fluoxetine improves outcomes in anxious school refusing adolescents (11-16.5 years). Sixty-two participants were randomly allocated to CBT alone, CBT + fluoxetine or CBT + placebo. All treatments were well tolerated; with one suicide-attempt in the CBT + placebo group. All groups improved significantly on primary (school attendance) and secondary outcome measures (anxiety, depression, self-efficacy and clinician-rated glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 34 publications
1
49
1
Order By: Relevance
“…One study reported two trials that were treated independently for analyses 55 and another compared a drug+CBT group vs. a placebo+CBT group and was therefore excluded from the drug and placebo response analyses 59 . Characteristics of the thirty-six included trials (sTable 1) and details regarding heterogeneity and publication bias (S3) can be found in the Supplemental Material.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported two trials that were treated independently for analyses 55 and another compared a drug+CBT group vs. a placebo+CBT group and was therefore excluded from the drug and placebo response analyses 59 . Characteristics of the thirty-six included trials (sTable 1) and details regarding heterogeneity and publication bias (S3) can be found in the Supplemental Material.…”
Section: Resultsmentioning
confidence: 99%
“…As noted above, Melvin et al. () found that after intervention some students improved significantly in their school attendance and emotional symptoms, but few were free of anxiety symptoms over the period of follow‐up. Other studies (Flakierska, Linstrom, & Gillberg,,; Kearney, ; McCune & Hynes, ) suggest that at least one‐third of young people who have presented with school refusal (as the term is used in the present paper) are likely to experience serious adjustment difficulties in adulthood.…”
Section: Prognosis and Relationship With Psychiatric Disorder In Adulmentioning
confidence: 87%
“…It was found that a significantly greater proportion of the medicated children achieved the target 75% attendance rate by the end of the treatment. However, given the health risks of this type of medication, and its limited impact in reducing adolescent depression (Hazell & Mirzaie, ), its use is not recommended (Melvin et al., ). Melvin et al.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct reference to different SAP types appeared in Broadwin's (1932) account of "a form of truancy ... [which] occurs in a child who is suffering from a deep-seated neurosis" (p. 254). Thereafter, efforts to identify SAP types burgeoned (e.g., Eisenberg, 1958;Kahn & Nursten, 1962;Partridge, 1939;Reid, 1985) and subdivisions within SAP types were also proposed. In the 1980s reviews of SR subtyping appeared.…”
Section: Differentiation Between Types Of School Attendance Problemsmentioning
confidence: 99%